Your Humble Servant: Agents in Early Modern Europe - Cools, Hans; Keblusek, Marika; Noldus, Badeloch (Hilversum Verloren, 2006)
In early modern Europe, agents were everywhere. They engaged in in the transmission of political news, were employed on diplomatic mission and negotiated economic, cultural and intellectual dealings between patrons and their clients. The agents' extensive networks, established in order to succeed professionally on one level, often provided them with an ideal resource for the execution of additional offices. This book presents agents from different professional groups - artists, soldiers, clergymen, diplomats, merchants and bankers - and explores the differences and similarities in their contacts, activities and backgrounds
Introduction: Profiling the Early Modern Agent / Marika Keblusek -- A Question of Attribution: Art Agents and the Shaping of the Arundel Collection / David Howarth -- Between Courts: The Colonna Agents in Italy and Iberia, 1555-1600 / Thomas James Dandelet -- Francesco Feroni (1614/16-1696): Broker in Cereals, Slaves and Works of Art / Hans Cools -- Loyalty and Betrayal: Artist-Agents Michel le Blon and Pieter Isaacsz, and Chancellor Axel Oxenstierna / Badeloch Noldus -- Political Brokerage in the Dutch Republic: The Patronage Networks of William Frederick of Nassau-Dietz / Geert H. Janssen -- Art and Information Brokerage in the Career of Don Giovanni de' Medici - Brendan Dooley -- Book Agents: Intermediaries in the Early Modern World of Books / Marika Keblusek -- The Art of the Dealer: Marketing Paintings in Early Modern Antwerp / Filip Vermeylen -- International Business Communication Patterns in the Dutch Commercial System, 1500-1800 / Jan Willem Veluwenkamp -- Sending a Letter Between Amsterdam and Stockholm: A Matter of Trust and Precautions / Heiko Droste
Keywords: Howard, Thomas -- 21st Earl of Arundel -- 1585-1646; Oxenstierna, Axel -- 1583-1654; Willem Frederik -- Graaf van Nassau-Dietz -- 1613-1664; Colonna family; House of Medici; 17th Century (1601-1700); 16th Century (1501-1600); Collecting; Translation; Fine art; Book; Patronage; Court; Netherlands; United Kingdom; Italy; Antwerp (Belgium)